The pattern recognition reagents RAGE VC1 and peptide p5 share common binding sites and exhibit specific reactivity with AA amyloid in mice. (2nd January 2016) - Kennel, Stephen J.; Williams, Angela; Stuckey, Alan; Richey, Tina; Wooliver, Craig; Chazin, Walter; Stern, David A.; Martin, Emily B.; Wall, Jonathan S.
Abstract: In the US, there remains a need to develop a clinical method for imaging amyloid load in patients with systemic, visceral amyloidosis. The receptor for advanced glycation end products (RAGE), which exists as a transmembrane receptor and soluble variant, is found associated with a number of amyloid deposits in man. It is unclear whether amyloid-associated RAGE is the membrane or soluble form; however, given the affinity of RAGE for amyloid, we have examined the ability of soluble RAGE VC1 to specifically localize with systemic AA amyloid in mice. We further compared the reactivity of RAGE VC1 with that of the synthetic, amyloid-reactive peptide p5. Methods : Binding of radiolabeled RAGE VC1 and p5 to synthetic amyloid fibrils was evaluated using in vitro "pulldown" assays in the presence or absence of RAGE ligands. Radioiodinated RAGE VC1 and technetium-99 m-labeled p5 were studied in mice with systemic AA amyloidosis using dual-energy SPECT/CT imaging, biodistribution and microautoradiography. Results : Soluble RAGE VC1 competed with radioiodinated peptide p5 for binding to rVλ6Wil, Aβ (1–40) and IAPP fibrils but not with the higher affinity peptide, p5R. Pre-incubation with AGE-BSA abrogated binding of VC1 and p5 to rVλ6Wil fibrils. Dual-energy SPECT/CT images and quantitative tissue biodistribution data showed that soluble RAGE VC1 specifically bound AA amyloid-laden organs in mice as effectively as peptide p5. Furthermore, microautoradiography confirmed that RAGE VC1 bound specifically to areas of Congo red-positive amyloid in mouse tissues but not in comparable tissues from control WT mice. Conclusion : Soluble RAGE VC1 and peptide p5 have similar ligand binding properties and specifically localize with visceral AA amyloid deposits in mice.